The Shallow Ecology Perspective on The Little Prince Novel By Antoine De Saint-Exupéry - Mutmainnah; Nurlailatul Qadriani (English Literature Study Program, Faculty of Humanities, Universitas Halu Oleo, 2025)
The narration about the bond between humans and nature in literary works is an element that is quite easy to find, but unfortunately this narrative does not seem to mean anything other than to evoke and dissolve the reader in the form of familiarize. The ecological perspective in Antoine de Saint-Exupéry's novel